2017
DOI: 10.24034/j25485024.y2013.v17.i3.2256
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengembangan Pelayanan Rawat Inap Puskesmas Berbasis Service Delivery System

Abstract: Community Health Center (CHC) is one of the public organization perceived by society, while its resource hasn’t sufficient. This lead to inpatient service provided hasn’t been maximal. This study purposes to identify the strengths, weaknesses, opportunities and threats and to formulate development strategies inpatient of CHC based on service delivery system in East Java. Analysis method of this study (a) applied interactive, (b) descriptive, (c) internal factors, (d) external factors, (e) external internal mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…9 In addition, non-medical administrative work was still concurrently held by paramedics, causing not maximum human resource performance. This finding was in line with Wibowo's, 10 study in 2011 that found many administrative work in health cares were held by health personnels, such as nurses or midwives, which indicated that nonmedical personnels in East Java health cares were still not enough.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…9 In addition, non-medical administrative work was still concurrently held by paramedics, causing not maximum human resource performance. This finding was in line with Wibowo's, 10 study in 2011 that found many administrative work in health cares were held by health personnels, such as nurses or midwives, which indicated that nonmedical personnels in East Java health cares were still not enough.…”
Section: Discussionsupporting
confidence: 85%
“…Performing administrative activities in health care with inpatient care by health personnels, such as nurses and midwives, would lead to a decrease in the concentration, be unfocused and decline health care performance in services to the public. 10 In line with this was findings of Handayani et al, 11 that there were 53.9 % of health care health workers got additional tasks, and 56.6% of the 53.9% stated that the additional tasks sometimes interfere with their main duties and functions in providing health care in the health care. In this case, additional non-medical worker through outsourcing patterns was necessary considering limited non-medical workers and budget available.…”
Section: Discussionmentioning
confidence: 55%
“…The population in this study were all Regional General Hospitals (RSUD), Regencies or Cities in East Java Province -Indonesia. Hospital sampling was determined based on a purposive technique by considering four cultural regions in East Java Province, namely Mataraman Culture, Arek Culture, Pandalungan Culture, and Madura Culture [13].…”
Section: Methodsmentioning
confidence: 99%
“…According to Wibowo (2019) the results of an external environmental analysis of the development of inpatient services at the Public Health Centre in East Java showed that all indicators of economic, legal, socio-cultural and technological variables were opportunities in developing inpatient services for the public health centre in East Java. 17…”
Section: Socioeconomic Effectsmentioning
confidence: 99%